Field Tests' Study of Deviation Correction of Building near Excavation - Xi Peng; Ningxin Yang; Mi Zhou (Advances in Civil Engineering)
Deviation correction of building is a big challenge for engineers. Without powerful technique for deviation, no special guidance can be followed to conduct the deviation rectification of buildings, which brings numerous failure cases. In this study, a case study was performed to provide insight into the behavior of a special technique for deviation rectification of building near excavation. The new technique was introduced firstly, and then, the field test data, in terms of lateral displacement of wall of pit, water level deviation, and soil deformation around pile of the building, were addressed to show the performance of the function of each process and the mechanism of it. The results show that this new technique for the deviation rectification of building works very well to uplift the whole building to reach the destination position (maximum uplift = 9.71 cm) and meets the requirement of design demand, without negative effect on the adjacent excavation reported.